SERAPAN SIANIDA (CN) PADA Mikania cordata (Burm.f) B.L. Robinson, Centrosema pubescens Bth DAN Leersia hexandra Swartz YANG DITANAM PADA MEDIA LIMBAH TAILING TERKONTAMINASI CN - Syarif, Fauzia (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2009)
Some plant species growing in the contaminated areas, indicated high toleranceand potentially affective in accumulating pollutants in their roots and above groundportions. These plants can be utilized as hyperaccumulators for cleaning up thecontaminated sites. Study on heavy metal and CN contamination and potentialplant species for accumulator is urgently needed in order to understand the problemsand to obtain suitable technology for the solution. This research aims to examineCN accumulator plants growing in CN contaminated tailing to find a possible solutionof cleaning up by using green technology of phytoremediation. Phytoremediation isdefined as clean up of pollutants primarily mediated by photosynthetic plants. Thisstudy aims to characterized plants that grow under extreme contaminated media ofgold mined tailing and to analyse their potencies as hyperaccumulators. Mikaniacordata (Burm.f) B.L.Robinson,Centrosema pubescens Bth and Leersia hexandraSwartz which proven tolerant and dominant in the contaminated site were examinedin this research. The plants were grown in tailing waste media added by 0 ppm CN,2.5 ppm CN, 5 ppm CN dan 7.5 ppm CN using complete randomized design with 5replicates. The results showed that the plants were capable of growing under thehighest level of CN. Among three species, Mikania cordata showed the highestbiomass production followed by Centrosema pubescens and Leersia hexandra. TotalCN accumulation varied between species, the highest was reached in 2.5 ppm CNtreatment i.e. 22.48 mg/kg in Leersia hexandra, followed by Centrosema pubescens(18.92 mg/kg) and Mikania cordata (12.03 mg/kg). The highest CN content was0.085 mg in Mikania cordata treated with 7.5 ppm CN. High ratio of shoot to root CN(>1) was expected in hyperaccumulator plants to indicate that CN was more distributedin the above ground portions than in the roots. In this study the highest shoo to rootCN ratio was showed in Mikania cordata i.e.11.75